Electrochemical sensor based on a silver nanowires modified electrode for the determination of cholesterol. Issue 13 (17th June 2015) - Xu, Lin; Hou, Yiting; Zhang, Mengdan; Cheng, Tao; Huang, Wei; Yao, Cheng; Wu, Qiong
Abstract : In this study, the fabrication of an amperometric cholesterol biosensor based on silver nanowires (AgNWs) and cholesterol oxidase (ChOx)–graphene oxide (GO)–chitosan (CS) film is reported. Abstract : In this study, the fabrication of an amperometric cholesterol biosensor based on silver nanowires (AgNWs) and cholesterol oxidase (ChOx)–graphene oxide (GO)–chitosan (CS) film is reported. The electrochemical behaviour of the ChOx/Ag/GO/CS/ITO biosensor was studied using cyclic voltammetry (CV), which revealed that the developed biosensor possessed high sensitivity (13.628 μA mM −1 cm −2 ) and a low detection limit (0.427 mg dL −1 ). The apparent Michaelis–Menten constant, K appM, of this biosensor was very low (2.813 mM), originating from the effective immobilization process and the nanowires structure of the substrate. The biosensor expressed a wide linear range up to 400 mg dL −1 in physiological conditions (pH 7.0), making it very promising for the clinical determination of cholesterol.